Determinación de Leucemia Viral Felina en gatos, en la clínica El Paraíso de las mascotas, Babahoyo - Estrella Basurto, Hugo Orlando (2023)
Feline leukemia is considered a viral disease that has a high impact and relevance, it promotes retroviral infections in domestic cats, in most cases, it is transmitted horizontally through direct contact of secretions that contain the virus. VLeF causes a state of immunosuppression, allowing the development of other diseases and neoplasias in cats. In this way, it becomes one of the most common causes of death among felines, and this is where the importance of knowing the development and how this pathology affects the environment of these animals lies. The objective of this study is to evaluate the presence of the feline leukemia virus in cats. In the “El Paraíso de las mascotas” clinic, in the city of Babahoyo, diagnoses were made through the application of the Anigen Rapid FIV Ab immunochromatography test. /FeLV Ag, to identify the virus antigen, thirty blood samples taken from the animals were analyzed, with prior consent from their owners. As a result of the statistical evaluation of different variables and risk factors, the incidence found in this research is 10% for feline leukemia from the sample taken.